SOCIETY, SEAFARING AND WATERCRAFT IN PREHISTORIC OCEANIA - Lukáš Petrík (Asian and African Studies)
Many islands in the Pacific were settled as the last habitable parts of the Earth, with their size and distance being the primary reasons. The settlement of these islands required vessels capable of transporting a sufficiently large group of people and their provisions over distances of hundreds to thousands of kilometres. Numerous books and studies have been dedicated to watercraft and voyaging in prehistoric Oceania, aiming to provide detailed descriptions and reconstructions. However, technological innovations in any field are driven by a specific set of norms that reflect the adaptive strategies of local communities and interactions amongst them. Technologies themselves do not exist as material products in a social vacuum but are, to some extent, social constructs framed by the history, traditions, and cultural norms of societies and their intricate relationships. This article serves as a reflective exploration of the specific social, demographic, and cultural phenomena in prehistoric Oceania, predominantly within the context of the Lapita culture. It examines the potential correlations and influences of these phenomena on the types of watercraft used and the voyaging practices. The primary objective of this article is to highlight these correlations, which can serve as a basis for testable hypotheses and subsequent research. In the absence of concrete empirical data, such research holds the potential to enrich our knowledge of seafaring, navigational techniques, and canoe usage in prehistoric Oceania, mainly during the Lapita and subsequent post-Lapita periods.